Epizootic and epidemiology features for leptospirosis in Ternopil region - Kravchuk, Y (Annals of Mechnikov’s Institute, 2020)
Introduction. Leptospirosis is the most widespread zoonotic diseases in the whole world. In Ukraine leptospirosis is registered practically in all regions, however very much unevenly, that it is related to the level of acidity of soils. One of such regions there is the Ternopil region. Materials and methods. Were based on official statistics of the incidence leptospirosis in the Ukraine regions and carried out anti-epidemic activities in 1984-2014. Results & discussion. Ternopil region was expressed of leptospirosis with epizootic and epidemic level. The level of morbidity of people in this region exceeded middle state index and hesitated within the limits of 1,05-12,17 on a 100 thousand population, the most getting up was on 1992-2001 for of the last 30 years. The level of morbidity is increase at the end of summer and in autumn (at most in September), that, probably, it is related to the increase of quantity of rodents and "bathing" season. The etiologic structure of leptospirosis in region was by L. rippotyphosa at 1981, in 90th – L. icterohaemorrhagiae, later were L. hebdomadis, canicоla and pomona, first – L. kabura and L. polonica, at the same time part of L.icterohaemorrhagiae grew short to 37,5 %, diseases, caused L. grippotyphosa, – rare and not annually. In 2010 diseases were predefined by L. icterohaemorrhagiae and L. canicоla, in 2011 – L. canicоla, L. icterohaemorrhagiae, L. pomona. In 2012 from 19 cases of 10 were caused by L. canicоla, in 2013 from 26 – 12, in 2014 from 35 – 7. From 2004, became more frequent the mixed leptospirosis, part of which in separate years arrived at 25-37 % among. The agricultural animals (cattle, pigs, horse) and dogs are the independent reservoir of leptospiras. The agricultural animals and possibility of transmission by alimentary way of causative agent were assist maintenance of continuous epizootic process an circulations of causative agent in an interepidemic period during great while without the receipt of leptospiras from a natural reservoir.Was present the direct correlation between temperature of air and level of morbidity of people (r=0,77) and the same between the amount of precipitations and level of morbidity (r=0,79). Conclusion. The abiotic (climatic-ground terms, temperature of air, amount of precipitations) and biotic factors (vegetation, quantity and infected of rodents, and also other warm-blooded owners) of were confirmed as nathural reservuar of leptospirosis. The difference of soils acidity makes territorial division of disease, because leptospira is survive in alkaline soils and die quickly in acid.